Interface Between Glacial Lake Outburst Floods and National Security in Nepal (National Security: A Journal of the National Defence University-Kenya, 2025)
This study investigates the implications of Glacial Lake Outburst Floods (GLOFs) on national security in Nepal, with a particular focus on their cascading effects on human security. The central research question guiding this inquiry is: How do GLOFs impact human security, and what are their cascading effects on national security in Nepal? A mixed-methods research approach was employed, utilising an explanatory sequential design. The quantitative component involved statistical analysis of secondary data and survey responses, focusing on the frequency and intensity of GLOFs and their impacts on infrastructure, livelihoods, and socio-economic stability. The qualitative component consisted of semi-structured interviews and focus group discussions with key stakeholders, including disaster management officials, climate experts, and community representatives, to contextualise and enrich the quantitative findings. The study was conducted across eight high-risk Himalayan districts. A sample of 450 respondents was determined using Cochran’s formula. In addition, three focus group discussions were conducted to gain deeper qualitative insights. The findings underscore the exacerbating influence of climate change and accelerated glacial melting in the Himalayas, which heighten the risks associated with glacier lake outburst floods (GLOFs). These events have profound consequences for human security, thereby contributing to broader national security vulnerabilities. The study identifies significant gaps in Nepal’s disaster risk management framework and calls for a paradigm shift in preparedness strategies. Recommendations include implementing comprehensive risk assessments, establishing robust early warning systems, developing climate-resilient infrastructure, and implementing community-based adaptation measures to enhance resilience.
Keywords: Climate change, disaster management, GLOFs, glacier melting, Himalayas, human security, Nepal